FINANCING THE INTERNATIONALIZATION OF SPANISH INDUSTRIAL SMES, 1980-2000: THE CASE OF THE GRIFOLS GROUP (Revista Galega de Economía)
There is not enough research on the role played by finance in the expansion of industrial firms, especially in the case of small and medium-sized enterprises (SMEs), which, since the 1980s, have had to face the challenges of the internationalization spurred on by the Second Globalization. In this article, we explore the subject through the Spanish case during the period 1980-2000 and offer new information extracted from databases and a relevant case study: the financial background behind the transformation of the Grifols Group from a medium-sized business into a large global corporation. According to our research, the â€œpecking orderâ€ induces the increasing reliance of large firms on public funding, which means more bank credit available for the SMEs. From the study of the Grifols case we learn that to have a strong international partner eases the access to credit for the SMEs